2013
DOI: 10.1111/jocn.12098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of motivational interviewing to promote weight loss in obese children

Abstract: This study indicates that motivational interviewing is a useful method for improving behaviour changes in eating, physical activity and weight loss for obese children, suggesting the benefits of such intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(81 citation statements)
references
References 40 publications
1
79
0
1
Order By: Relevance
“…However, this observational finding is essentially what the emerging literature on using motivational interviewing describes. [37][38][39] The fact that interventions using motivational interviewing have demonstrated efficacy makes this parallel finding in normal weight children all the more interesting. Confidence and self-efficacy of parents have been described in the literature as important for sustained behavior change in childhood obesity, 40,41 but no study has identified or discussed the finding of intrinsic motivation in children.…”
Section: Discussionmentioning
confidence: 99%
“…However, this observational finding is essentially what the emerging literature on using motivational interviewing describes. [37][38][39] The fact that interventions using motivational interviewing have demonstrated efficacy makes this parallel finding in normal weight children all the more interesting. Confidence and self-efficacy of parents have been described in the literature as important for sustained behavior change in childhood obesity, 40,41 but no study has identified or discussed the finding of intrinsic motivation in children.…”
Section: Discussionmentioning
confidence: 99%
“…The weight loss interventions also varied from providing a single intervention (n = 5): Dietary (Rosado, Arellano, Montemayor, GarcĂ­a, & Caamaño, 2008 [two interventions]), or physical activity (Farpour-Lambert et al, 2009;Lazaar et al, 2007;Maddison et al, 2011). A majority of the studies (n = 14) used a combination of strategies: education and behavior (Wong & Cheng, 2013 (Carrel et al, 2005;Davis, Ventura, Cook, Gyllenhammer, & Gatto, 2011;Harder-Lauridsen et al, 2014); diet and education (Rosado et al, 2008); diet, physical activity, and behavioral changes (Adam, Westenhofer, Rudolphi, & Kraaibeek, 2009;Croker et al, 2012;Janicke et al, 2008;Korsten-Reck, Kromeyer-Hauschild, Wolfarth, Dickhuth, & Berg, 2005;Maddison et al, 2014;Reinehr, 2010;Satcher et al, 2010) (see Table S3, available with online version of this article).…”
Section: Treatment the Type Of Weight Loss Interventions In The 16mentioning
confidence: 99%
“…More recently, MI has shown positive results in weight loss efforts across populations (Christie & Channon, 2013) and has had successful outcomes across the lifespan (Flattum, Friend, Neumark-Sztainer, & Story, 2009; Meybodi, Pourshrifi, Dastbaravarde, Rostami, & Saeedi, 2011; Wong & Cheng, 2013). Recent studies suggest that MI is effective even by telephone.…”
Section: Introductionmentioning
confidence: 99%